The role of environmental knowledge: Predictor for environmental attitude among biology students at Universitas Negeri Malang? - Kundariati, Maisuna; Putra, Zia Aulia Zaidin (Univeritas Papua, 2025)
Environmental issues have been extensively discussed worldwide, including in Indonesia. Various human activities contribute to environmental degradation, affecting soil, water, and air quality. This study investigates environmental knowledge, environmental attitudes, and the relationship between environmental knowledge and attitudes among biology students at Universitas Negeri Malang (N = 126). Conducted in November 2020 in Malang, Indonesia, this study employed purposive sampling to select participants. Data were collected using a questionnaire and analyzed through descriptive quantitative methods and simple linear regression. The results indicate that students exhibit a high level of environmental knowledge and attitudes. Moreover, a moderate positive correlation (R = 0.427) was observed between environmental knowledge and attitudes. The linear regression analysis yielded the equation (Y = 2.211 + 0.488X), demonstrating that environmental knowledge contributes 18.2% to variations in environmental attitudes. These findings suggest that while knowledge of environmental issues is crucial, fostering active engagement in sustainable practices and advocacy is essential to strengthening environmental attitudes.